The application of multimedia messaging services (MMS): online ordering system / Noor Suhaini Mila Suparman - Suparman, Noor Suhaini Mila (2004)
This project entitled Online Ordering System describes an application through mobile phone emulator. It provides the user with ordering services where the user may simply order a list of items on the mobile phone without having to go out for shopping. This is one of Multimedia Messaging Services (MMS) applications. VAS is the main interface which handless the MMS application. VAS may provide services such as purchasing items through mobile phone. This situation held when the provider sets up a VAS application which generates multimedia messages and sends them to one or multiple recipients. In many cases, the user need to first subscribe to the VAS in order to receive corresponding messages. This subscription can be performed by sending a message to the VAS application. In order to operate a VAS, the VAS provider has to establish a service agreement with the MMS provider. The supplier in this project is known as the server while the client is the user. This project is developed using Java 2 Micro Edition. It is a suitable program in creating this application. All the information in the server is stored in the database table structure. The user just needs to place the order with cell phone. In this project, the ordering process information shown in the cell phone is represented by the emulator.